Pengaruh Model Pembelajaran Open -Ended Berbantuan Media Sanakpilian Terhadap Kemampuan Berfikir Kritis Matematika - Aisyah, Irma Antonia; Mardiana, Tria; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of theLearning Model with the Open-ended help of relatives on the ability to think critically in mathematics in fourth grade students of SDN Dukun 02, Magelang district. This study uses a pre-experimental design with a one group pretest posttest design model. Research subjects were selected by non- probability sampling saturated sampling model. Samples were taken as many as 15 students, using data collection methods in the form of description tests and performance tests of students’ critical thinking skills. prerequisite test for critical thinking skills using theformula. The Kolmogorov Smirov, validity test for the description test uses theformula Pearson. Reliability test usingformula cornbach’s alpha with the help of SPSS For Windows. In addition, the researchers also used the level of difficulty test and the test of discriminating power. Analysis of the data usingstatistical techniques, non-parametric namely by using Wilcoxon test. The results showed that the calculation of the average value of the posttest description test was 71.25 which was greater than the pretest value with an average value of 48.75, the calculation of performance assessment in the pretest activity was 65 and the posttest was 72.5. this is evidenced by the results of the Microsoft excel and the next result of the Wilcoxon test analysis with a significant value of 0.01 <0.05, which means that there is a significant difference between the results of the pretest and posttest using an open ended learning model assisted by relatives’ media. The results of this study can be concluded that the use of sanakpilian media assisted by sanakpilian media has a significant effect on students’ critical thinking skills in learning mathematics.